Complete chloroplast genome sequence of the Oriental oak, Quercus variabilis (Fagaceae) - Xinbo Pang; Suran Wu; Hongshan Liu; Xiaohui Jiang; Zhihai Su; Guowei Zhang; Lijia Wang; Bin Li (Mitochondrial DNA. Part B. Resources, 2019)
Quercus variabilis plays a key role in soil remediation, erosion control, and in the economic and ecosystemic development in eastern Asia. In this study, we sequenced the complete chloroplast genome of Q. variabilis based on next-generation sequencing and used these data to assess genomic resources. The size of the Q. variabilis chloroplast genome is 161,168 bp, including a large single-copy region (90,464 bp), a small single-copy region (19,070 bp), and a pair of inverted repeats regions (25,817 bp). The overall GC content of the Q. acutissima chloroplast genome was 35.7%. The chloroplast genome of Q. variabilis encodes 112 different genes, including 78 protein-coding genes, 30 transfer RNAs (tRNA) and four ribosomal RNAs (rRNA). A phylogenetic tree constructed based on complete chloroplast genome sequences of 15 Quercus species showed that Q. variabilis was sister to Q. acutissima.